The sea of grass - Richter, Conrad, 1890-1968 (A. A. Knopf, 1937)
St. Louis woman travels to New Mexico to wed rancher, only to find that his first love is "sea of grass" where thousands of cattle roam and open-range cattlemen fight against small-town farmers.